Introduction of a metabolic joint asymmetry score derived from conventional bone scintigraphy - Ezziddin, S.; Khalaf, F.; Seidel, M.; Al Zreiqat, A.; Wilsmann-Theis, D.; Simon, B.; Biersack, H.-J.; Sabet, A. (Nuklearmedizin - NuclearMedicine, 2015)
Aim: Clinical differentiation of psoriatic arthritis (PsA) and rheumatoid arthritis (rA) based on the pattern of joint involvement can be difficult; the frequent form of PsA with polyarthritis of the peripheral joints may sometime resemble rA. We investigated a metabolic joint asymmetry score (MJAS), reflecting the overall asymmetric joint involvement on conventional bone scintigraphy, for differentiating PsA from rA in patients presenting with peripheral polyarthritis. Patients, methods: 106 patients (n = 61, PsA; n = 45, rA) with peripheral polyarthritis (≥ 5 joints) as well as 26 control subjects with no history of chronic joint disorders were analyzed. The intensity of articular 99mTc-MDP uptake in 40 peripheral joint pairs was scored regarding the bilateral difference of each joint based on a scale of 0–2 (no significant, moderate, and marked asymmetry, respectively). The patient's MJAS was defined as the sum of uptake difference scores of all joint pairs. The association of MJAS with the underlying condition (Psoriasis criteria, Revised Criteria of the ACR) was examined. Results: 5280 peripheral joint pairs were investigated. There was no significant difference in the total number of involved joints in PsA 15.0 ± 8.2 versus rA 17.5 ± 8.8 patients (p = 0.132), but significantly less involvement in the control group (6.7 ± 5.0, p < 0.001). MJAS was markedly higher in PsA (17.0 ± 9.6) than in rA (4.8 ± 3.9, p < 0.001), and correlated with the total number of involved joints in PsA (r = 0.516, p < 0.001), but not in rA (r = 0.078, p = 0.380). The MJAS disparity between PsA and rA persisted after exclusion of the DIP joints (14.4 ± 7.7 vs. 4.4 ± 3.3; p<0.001). Conclusions: The new reproducible semi-quantification method for the asymmetry of metabolic joint involvement permits differentiation of psoriatic from rheumatoid peripheral arthritis with MJAS being markedly higher in patients with PsA as compared to rA patients. The score may offer an effective complementary tool for characterizing patients with peripheral polyarthritis.
Keywords: Psoriatic arthritis; rheumatoid arthritis; bone scintigraphy